By-Product Formation in a Trichlorosilane-Hydrogen System for Silicon Film Deposition. (1st January 2015) - Habuka, Hitoshi; Sakurai, Ayumi; Saito, Ayumi
Abstract : The process of by-product formation during silicon film deposition using trichlorosilane gas was studied by two types of the in situ measurement techniques, such as the langasite crystal microbalance (LCM) and the quadrupole mass spectra (QMS) analyzer, installed at the exhaust of the chemical vapor deposition (CVD) reactor. With the increasing hydrogen gas concentration, the QMS showed that the partial pressure related to SiCl2 decreased. Simultaneously, the deposition on the LCM surface decreased. Because SiCl2 gradually produces the burnable by-product of (SiCl2 ) n, an oily silane, at the exhaust, the CVD parameters effective for suppressing the SiCl2 formation were evaluated.